2017
DOI: 10.1002/pi.5412
|View full text |Cite
|
Sign up to set email alerts
|

Influence of diisocyanate, glycidol and polyol molar ratios on the mechanical and thermal properties of glycidyl-terminated biobased polyurethanes

Abstract: A series of epoxy-terminated polyurethanes (EPUs) were synthesized from castor oil, 4,4 ′ -methylenebis(cyclohexyl isocyanate) (H 12 MDI) and 2,3-epoxy-1-propanol (glycidol) by changing the molar ratio of H 12 MDI to glycidol to polyol. Fourier transform infrared, 1 H NMR and solid-state CP/MAS 13 C NMR spectroscopic analyses revealed the presence of epoxy linkages within the polyurethane backbone. Thermogravimetric analysis showed that EPU4 with a polyol:diisocyanate:glycidol molar ratio of 1:6:6 exhibited an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…where mp and ms represent the masses of the polyurethane and solvent (g), respectively, ρp and ρs are the densities of the polyurethane and solvent (g/cm 3 ), respectively, R and T are the gas constant (8.314 J/K·mol) and absolute temperature (K), respectively, and δs is the solubility parameter of the solvent (J/cm 3 ). The variable δp (J/cm 3 ) was determined by fitting the curves of the swelling coefficients (Q) versus the solubility parameter (δ) (Mathew et al 2017). The corresponding abscissa value at the top of the curve was determined as δp in Fig.…”
Section: Cross-linking Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…where mp and ms represent the masses of the polyurethane and solvent (g), respectively, ρp and ρs are the densities of the polyurethane and solvent (g/cm 3 ), respectively, R and T are the gas constant (8.314 J/K·mol) and absolute temperature (K), respectively, and δs is the solubility parameter of the solvent (J/cm 3 ). The variable δp (J/cm 3 ) was determined by fitting the curves of the swelling coefficients (Q) versus the solubility parameter (δ) (Mathew et al 2017). The corresponding abscissa value at the top of the curve was determined as δp in Fig.…”
Section: Cross-linking Densitymentioning
confidence: 99%
“…3 (a). The corresponding abscissa values at the top of the curves were fitted by Gauss and were determined as the solubility parameter (Valero et al 2009;Mathew et al 2017). It was found that the abscissa corresponding to the maximum value of the ordinate was 18.7 (J/cm 3 ) 1/2 (Zhu et al 2011).…”
Section: Cross-linking Density Of the Pufsmentioning
confidence: 99%
“…Analysis of FTIR spectra in the area of carbonyl valence vibrations (wave number interval ν = 1600-1760 cm -1 ) revealed important features of structural organization of studied objects (Figure 2). The results of spectral studies of some similar polymers with urethane groups were used to classify the corresponding absorption bands [26,27].…”
Section: Resultsmentioning
confidence: 99%
“…The SNPs (0.3 wt %) are dispersed in dehydrated castor oil via ultrasonication method and is added into the heated H 12 MDI kept in a three necked round bottom flask. The detailed procedure for the synthesis of PU and PE are described in the previous works . Further, 10 wt% of HTPDMS was added into the viscous PE solution containing SNPs, followed by the addition of γ‐APS (0.01%) coupling agent and DBTDL.…”
Section: Methodsmentioning
confidence: 99%